Effect of Cigarette Smoking on HDL-C in Adolescent (Bangladesh Medical Journal, 2011)
Key words: cigarette smoking; HDL-C; adolescentDOI: 10.3329/bmj.v39i2.7033Bangladesh Medical Journal 2010, 39(2) pp.26-29